The DREAM complex mediates GIST cell quiescence and is a novel therapeutic target to enhance imatinib-induced apoptosis - Boichuk, Sergei; Parry, Joshua A.; Makielski, Kathleen R.; Litovchick, Larisa; Baron, Julianne L.; Zewe, James P.; Wozniak, Agnieszka; Mehalek, Keith R.; Korzeniewski, Nina; Seneviratne, Danushka S.; Schöffski, Patrick; Debiec-Rychter, Maria; et al. (Cancer research, 2013)
Gastrointestinal stromal tumors (GIST) can be successfully treated with imatinib mesylate (Gleevec); however, complete remissions are rare and patients frequently achieve disease stabilization in the presence of residual tumor masses. The clinical observation that discontinuation of treatment can lead to tumor progression suggests that residual tumor cells are, in fact, quiescent and, therefore, able to re-enter the cell-division cycle. In line with this notion, we have previously shown that imatinib induces GIST cell quiescence in vitro through the APCCDH1-SKP2-p27Kip1 signaling axis. Here, we provide evidence that imatinib induces GIST cell quiescence in vivo and that this process also involves the DREAM complex, a multisubunit complex that has recently been identified as an additional key regulator of quiescence. Importantly, inhibition of DREAM complex formation by depletion of the DREAM regulatory kinase DYRK1A or its target LIN52 was found to enhance imatinib-induced cell death. Our results show that imatinib induces apoptosis in a fraction of GIST cells while, at the same time, a subset of cells undergoes quiescence involving the DREAM complex. Inhibition of this process enhances imatinib-induced apoptosis, which opens the opportunity for future therapeutic interventions to target the DREAM complex for more efficient imatinib responses. Cancer Res; 73(16); 5120-9. ©2013 AACR.